A geratividade do comportamento verbal : divergências entre as propostas de B. F. Skinner e N. Chomsky - Bandini, Carmen Silvia Motta (Universidade Federal de São Carlos, 2008)
One of the most interesting questions in the study of the language is its original character. Any philosophy or science that tries to explain language must account for this peculiar characteristic. Radical Behaviorism of B. F. Skinner and the theory of Generative-Transformational Grammar of N. Chomsky were very important sources of explanation of language phenomena during the 20th Century. Chomsky was one of the most famous critics of Skinnerian behaviorism. His review of Skinner s Verbal Behavior was probably more known around the world than Skinner s original book. In this review, Chomsky asserts that the operant model can not explain the original character of language. However, recent works have shown that Skinner tries to consider this characteristic when he talks about language. Within this context, the present dissertation intended to investigate Skinner s treatment of the creative processes of verbal behavior, set against Chomsky's theory. This work also tried to search the conceptual categories used by Chomsky to criticize Skinner and use this conceptual categories to improve the analysis of Skinner s text. In addition, this dissertation also attempted an internal analysis of Skinnerian concepts involved in the explanation of verbal behavior, as well as an assessment of the truth or falseness of Chomsky s critical work. We found three conceptual categories used by Chomsky in his Review of Skinner s Verbal Behavior. The survey of such categories allowed a fruitful analysis of Skinnerian account of the generative character of verbal behavior. It is argued that Chomsky committed many conceptual mistakes in his Review and because of these mistakes his work cannot prove that Skinnerian analysis of verbal generativity is impracticable. It is also argued that Skinnerian theory about verbal (and not verbal) generativity does not seem to be in any contradiction to the philosophy of science that Skinner adopts. We then conclude that, from the theoretical standpoint, the behaviorist explanation of verbal behavior and its generativity can configure an useful model.
Keywords: Behaviorismo radical; Comportamento verbal; Comportamento verbal novo; Gramática gerativa; Gramática transformacional; Gramática gerativa-transformacional; Verbal behavior; Verbal generativity; Radical behaviorism; Generative-transformational Grammar; CIENCIAS HUMANAS::FILOSOFIA